2012
DOI: 10.1097/fjc.0b013e318270b968
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Cyclooxygenase-2 Inhibition in Limiting Abdominal Aortic Aneurysm Progression in Mice Correlates With a Differentiated Smooth Muscle Cell Phenotype

Abstract: Abdominal aortic aneurysms (AAAs) are a chronic condition that often progress over years to produce a weakened aorta with increased susceptibility for rupture, and currently, there are no pharmacological treatments available to slow disease progression. AAA development has been characterized by increased expression of cyclooxygenase-2 (COX-2), and inactivation of COX-2 before disease initiation reduces AAA incidence in a mouse model of the disease. The current study determined the effectiveness of COX-2 inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 35 publications
0
22
0
1
Order By: Relevance
“…Previous research has suggested that VSMC phenotypic modulation in response to inflammatory stimuli plays a major role in the development of atherosclerosis and IA. The modulation is mediated, in part, by TNF-α [39, 40]. Animal studies of VSMCs support this idea.…”
Section: Evidence That Nsaids Prevent Ia Rupturementioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has suggested that VSMC phenotypic modulation in response to inflammatory stimuli plays a major role in the development of atherosclerosis and IA. The modulation is mediated, in part, by TNF-α [39, 40]. Animal studies of VSMCs support this idea.…”
Section: Evidence That Nsaids Prevent Ia Rupturementioning
confidence: 99%
“…Animal studies of VSMCs support this idea. VSMCs isolated from a mouse model of AAA have reduced levels of contractile phenotypic markers α-actin, desmin, and SM22α [39]. COX-2 mRNA expression in VSMCs was upregulated in both rodent and human AAA and IA studies [13, 39, 41].…”
Section: Evidence That Nsaids Prevent Ia Rupturementioning
confidence: 99%
See 2 more Smart Citations
“…(58) In a mouse model of abdominal aortic aneurysms, we have previously determined that the effectiveness of cyclooxygenase-2 (COX-2) inhibition for limiting the progression of these aneurysms is associated with maintenance of a differentiated SMC phenotype. (9, 10) Therefore, targeting the specific COX-2-dependent pathway responsible for reducing differentiation may provide a strategy for reversing alterations to the differentiated SMC phenotype that contribute to the development of vascular pathologies.…”
Section: Introductionmentioning
confidence: 99%